Review on Impulse-Generated High-Energy Charged Particles in the Magnetosphere: Wave polarization and conductivity effects in the magnetosphere (Journal of Advances and Scholarly Researches in Allied Education, 2017)
The drift-bounce instability growth rate becomes smaller during the wave temporal evolution, and the instability undergoes stabilization when the wave frequency coincides with the toroidal eigenfrequency. The total amplification of the wave can be estimated as e γ τ˜ , where γ˜ is the wave growth rate at the beginning of the process, when it has its maximum value. The wave amplitude can increase only within a time ∼τ, when it is poloidally polarized. After this time, when the wave becomes to be toroidally polarized, it goes damped because of the finite ionosphere conductivity. This is in qualitative agreement with the recent radar experimental data.